Chapter V: local arts, food & cultures / Muhamad Hafiz Hassan and Mohd Asraf Ayob - Hassan, Muhamad Hafiz; Ayob, Mohd Asraf (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Travelling to places around the globe makes us see beyond our limitations, but local foodies will linger in our minds when we leave. Indonesia, is a well-known country in Southeast Asia, may offer a variety of delightful foods and mouthwatering beverages. Talking about local cuisine, Indonesia is one of the foodie paradises. A trip to Pontianak, West Kalimantan, Indonesia, was complete with tasting their local authentic culinary touch and unique street delicacies.